Internal Control'S Effect On Health Workers' Performance In Puskesmas, Sidoarjo - sihombing, abygael vrisca damarise; Triani, Ni Nyoman Alit (International Environmental Conferrence on Biosustainability Advancement, 2024)
The purpose of this study is to determine how the control environment, control activities, risk assessment, information and communication, also monitoring affect the performance of health workers at the Sidoarjo Health Center, known as Puskesmas (Pusat Kesehatan Masyarakat). Population of this studies consists of health workers in the Sidoarjo district. The total number of respondents who completed the research questionnaire was 114, all of them were health workers at Puskesmas in Sidoarjo district. This study employs quantitative research methods with primary data sources gathered via questionnaire. Using the SPSS version 25 as statistical tool, the data analysis strategy employs several linear regression models. According to the findings of this study, several factors such as control activities, information and communication, and monitoring have a positive and significant effect on the performance of the health workers at Puskesmas in Sidoarjo. Meanwhile, the control environment and risk assessment had no effect on the performance of the health workers at Puskesmas in Sidoarjo.